(untitled) (Fiep Bulletin - online, 2013)
Regular physical activity is important to health promotion and its practice has been encouraged in programs developed to control chronic diseases. Objective: evaluate the impact of the “Se Mexe Pinhal” program in the participants’ health. Method: From the clinical records of the 351 participants we obtained information on body mass index, cholesterol and glucoses serum levels, systolic and diastolic blood pressures in the initial, intermediary, and final periods of the study. Participants were classified in terms of their level of physical activity according to Matsudo Classification. To compare periods we adopted Friedman and Wilcoxon tests. Results: Among the participants, 52 (15%) were considered physically inactive and 298 (85%) irregularly active. Along the period of study, there were statistically significant decreases in the body mass index (p < 0,001) and in systolic (p < 0,05) and diastolic (p < 0,001) blood pressures. Glucose serum levels decreased from the beginning to the intermediary period (Wilcoxon test: p < 0,005) and returned to the initial levels in the final period (p < 0,005). Conclusion: The results showed the relevance of physical activity to prevent diseases, even though irregularly performed. Also, they can be seen as motivation to the implementation of program changes, so it can accomplish its goal in improving the participants quality of life.